2000
DOI: 10.1038/sj.leu.2401866
|View full text |Cite
|
Sign up to set email alerts
|

Relapse in childhood acute lymphoblastic leukemia is associated with a decrease of the Bax/Bcl-2 ratio and loss of spontaneous caspase-3 processing in vivo

Abstract: Dysfunction of the p53/Bax/caspase-3 apoptosis signaling pathway has been shown to play a role in tumorigenesis and tumor progression, ie the development of acquired drug resistance. Low expression of the apoptosis inducer Bax correlates with poor response to therapy and shorter overall survival in solid tumors. In the present study, we analyzed the p53/Bax/caspase-3 pathway in a paired and an unpaired sample series of children with acute lymphoblastic leukemia (ALL) at initial diagnosis and relapse. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
138
2
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(147 citation statements)
references
References 39 publications
4
138
2
3
Order By: Relevance
“…5,39 Cytochrome c forms an active complex with APAF-1, which recruits procaspase-9 and thereby leads to the final execution of the cell death by activating the downstream caspase cascade. 3,[7][8][9][10][11][12] The BAX/APAF-1/Caspase pathway of apoptosis may also be functional in death receptor triggered apoptotic cell death. This process presumably involves a Bid-dependent pathway leading to a conformational change in BAX.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,39 Cytochrome c forms an active complex with APAF-1, which recruits procaspase-9 and thereby leads to the final execution of the cell death by activating the downstream caspase cascade. 3,[7][8][9][10][11][12] The BAX/APAF-1/Caspase pathway of apoptosis may also be functional in death receptor triggered apoptotic cell death. This process presumably involves a Bid-dependent pathway leading to a conformational change in BAX.…”
Section: Discussionmentioning
confidence: 99%
“…5 Cytochrome c forms an active complex with APAF-1 that recruits procaspase-9 and thereby leads to the final execution of the cell death by activating the downstream caspase cascade. 3,[7][8][9][10][11][12] We have shown previously that loss of BAX expression correlates with a poor prognosis in patients with hepatic metastases of colorectal cancer undergoing surgical resection of liver metastases. 13 Similar data were obtained in diffuse aggressive nonHodgkin-lymphoma, 14 ovarian, 15 pancreatic 16 and esophageal cancer 17 where reduced BAX expression was also observed to be a negative prognostic factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the predictive value of the expression level of various Bcl-2 family members in ALL at diagnosis. [35][36][37][38][39][40][41][42][43][44][45] The majority of these studies indicate that steady-state levels of individual Bcl-2 family members are not optimal predictors of outcome 35,36,38,39 or ex vivo GC-sensitivity. 37,40,42 On the other hand, several studies using cell viability assays have demonstrated that ex vivo GC-sensitivity has a predictive value in relation to the short-term response to systemic GC monotherapy and to the long-term clinical outcome in response to combination chemotherapy.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…127 Other possible causes include the deregulation of the mitochondrial apoptosome, 67 especially the members of the Bcl-2 family which may show considerable intra-and interdisease variability, eg in lymphoma, 128 and may shift to an apoptosis-refractory profile when resistance develops. 129 Recently, an IAP-neutralizing and therefore apoptosis-promoting mitochondrial protein, termed Leukemia Smac/Diablo, has been identified that obviously plays a critical role in antagonizing the caspase-inhibitory effect of IAPs. 130,131 The role of Smac in tumor biology is as yet unclear but inactivation of this novel player could also result in a resistant phenotype.…”
Section: Death Ligands In Cancer Therapymentioning
confidence: 99%